(untitled) (The Journal of Ad-din Women’s Medical College, 2023)
Introduction: Diabetes is a major health issue in Bangladesh, with 8% of the population claiming 3% of all deaths. Diabetic foot ulcer (DFU) is a common complication of DM, with 9-26 million patients worldwide each year. High blood sugar levels and smoking can lead to DFU-I and foot-related complications, leading to amputation. MDR-resistant micro-organisms can form biofilm in infection-wound sites, making it diflcult to clean. Systemic antibiotic use can lead to increased mucosal permeability and hyper inflammation (collateral damage). This study aimed to provide cost-effective treatment for DFU-I to establish evidence of its usefulness and cure rates, with NaOCl 0.05% as the ideal and cost effective alternative. Objective: To compare two locally applied antiseptic applications (NaOCl 0.05% Vs. Povidone Iodine 10%) as the treatment outcome of DFU-I in clearing polymicrobial infection by enhancing healing process. Methodology: This cross-sectional observation study (clinico-epidemiological) was conducted among 41 adult diabetic foot ulcer infection patients (DFU-I). Patients of DFU-I studied at 4P Diabetes Care at daytime oflce hours (9AM to 9 PM except Fridays) during January 2021 to July 2022. Data were collected by using a hybrid designed questionnaire (close and open ended). Results: Most of these patients (42%) belonged between 51-60 years age group who suffered from diabetes for <10 days, followed by 39% for 10-19 days, and 19% for >=20days, respectively. Of 41 patients, 46% had been diagnosed with ulcer on anterior, dorsal, foot; 32% patient on phalanges and 22% on ankle. More than half (54%) of all DFU-I patients took <24 hours to cover disinfection process. Finding also showed that, 41% patient took >21 days, 22% patient took 18-21days and 37% patient took <17days for healing their wound. Our study revealed a significant relation between treatment and age groups of patients (p=0.03), period of DM (p=0.05), having co-morbidities (p=0.02), disinfection hours (p=0.03) and healing time, respectively. Conclusion: This study found that Sodium hypochlorite 0.05% was more effective, quicker and cheaper in treating polymicrobial diabetic infections than that of with 10% povidone iodine. However, this preliminary finding should not be taken as final until more advanced studies are conducted to accept or refute this study. The Journal of Ad-din Women’s Medical College; Vol. 10 (2), July 2022; p 31-41